â€œHILANG DI MATEâ€ TERINSPIRASI DARI KESENIAN TRADISI LISAN NANDONG DI DESA RAWAJADI KECAMATAN RENGAT KABUPATEN INDRAGIRI HULU - Ridho Zani; Susandra Jaya; Ediwar Ediwar (Jurnal Musik Etnik Nusantara, 2024)
In the Malay community in the city of Rengat, the oral tradition is called Nandong, which in oral literature is used to put children to sleep, usually conveyed with poetry or rhymes and sung rhythmically or humming, this is because Malay culture is always synonymous with poetry or rhymes. Based on the results of the artist's analysis of Nandung art, the artist found uniqueness in the rhythm which has vibrations or vibrato in the swing of the sentences. Then the creator also saw the strength of the poetry or rhyme found in Nandung, where the poetry or rhyme contained in the pantun contained a moral utterance or message conveyed. This is the idea in creating musical compositions using a traditional approach. The author divides it into two parts, beginning and end. In the first part, the focus is on presenting the Nandong pantun as an opening to start this composition, then we move on to the pantun that the author developed accompanied by melodic instruments using working techniques. The author presents the final part of this composition with a work that has developed a vocal melody into a varied and melodic playing, especially on the vocals and rhythm patterns that the author has developed using the work technique.